Cognition in Parkinson's disease - Narayanan, Nandakumar; Albin, Roger L. (Progress in brain research, 2022)
Cognition in Parkinson's Disease, Volume 269 in the Progress in Brain Research series, highlights new advances in the field, with this new volume presenting interesting chapters on a variety of timely topics, including Cognition in Prodromal Parkinson's disease, The epidemiology of cognitive function in Parkinson's disease, Real-life consequences of cognitive dysfunction in Parkinson's disease, Animal models of cognition in Parkinson's disease, Functional neuroanatomy of cognition in Parkinson's disease, Neuroimaging approaches to cognition in Parkinson's disease, Cognitive dysfunction and neuropsychiatric aspects of Parkinson's disease, Neuropsychology of Parkinson's disease, Cholinergic Systems, Attentional-Motor Integration, and Cognitive Control in Parkinson Disease, and much more.